The Flower Garden Banks Siderastrea siderea coral as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - DeLong, Kristine L; Palmer, Kylie; Wagner, Amy J; Weerabaddana, Mudith M; Slowey, Niall; Herrmann, Achim D; Duprey, Nicolas; Martínez-García, Alfredo; Jung, Jonathan; Hajdas, Irka; Rose, Neil L; Roberts, Sarah L; et al.
The proposed Anthropocene Global Boundary Stratotype Section and Point (GSSP) candidate site of West Flower Garden Bank (27.8762°N, 93.8147°W) is an open ocean location in the Gulf of Mexico with a submerged coral reef and few direct human impacts. Corals contain highly accurate and precise (<±1 year) internal chronologies, similar to tree rings, and their exoskeletons are formed of aragonite and can be preserved in the rock record. Here we present results from a large Siderastrea siderea coral (core 05WFGB3; 1755–2005 CE) sampled with annual and monthly resolutions that show clear markers of global and regional human impacts. Atmospheric nuclear bomb testing by-products ( 14 C, 239+240 Pu) have clear increases in this coral starting in 1957 for 14 C and the first increase in 1956 for 239+240 Pu (potential bases for the Anthropocene GSSP). Coral δ 13 C declined especially after 1956 consistent with the Suess effect resulting from the burning of fossil fuels. Coral skeletal δ 15 N starts to increase in 1963 corresponding with the increase in agricultural fertilizers. Coral Hg concentrations (1933–1980) loosely track fluctuations in industrial pollution and coral Ba/Ca increases from 1965–1983 when offshore oil operations expand after 1947. Coral temperature proxies contain the 20th-century global warming trend whereas coral growth declines during this interval.